Anonymous Modern Design Education in Western China: A Case Study - Wang, Zhiyong (Design and Technology Education: An International Journal, 2024)
Along with the rapid development of Chinese modern design since the 1980s, modern design education has grown in China. Many studies have already been conducted to examine the key aspects of this historical phenomenon, e.g., heroic figures and well-known institutes. This article, however, investigates the anonymous activities of modern design education in Western China that have long been ignored because of their mundane function. Methods such as document analysis, questionnaire, interview, and subjective understanding are used to achieve the goal of this article. Through research on the School of Fine Arts in a University of Science and Engineering in Western China, as a typical case, this article reveals that although the school lags behind many other design schools, modern design education at the school has experienced sustained growth since its rise in the twenty-first century. The school has made achievements in a difficult situation but suffers from a series of disadvantages and problems. Additionally, modern design education at the school is facing new challenges resulting from changes related to raised standards and intense competition. In conclusion, the value of relatively unknown educational organisations of modern design is becoming clearer, since they are closely connected to the everyday life of ordinary people in Western China and take on a great deal of responsibility in serving the general populace and the vulnerable groups in society. This article, therefore, tries to call attention to anonymous modern design education whose aspects are disclosed through a case study.